Molecular Properties, Bioactivity Scores, and Toxicity Predictions of the Phytoconstituents Present in Bauhinia Acuminata - Kudumula, Neelima; Divya, Noota; Sravika, Nagamalla; Priya, Saketha; Anusha, Pachava; Sai Jyotsna, Mudavath (International Journal of Scientific Research and Management (IJSRM), 2021)
ABSTRACT:To develop the herbal drug with the least side effects, there are superior opportunities to discover the medicinal and other biological properties. Natural products serve as sources of beneficial chemical molecules. For this study, Bauhinia acuminata an important medicinal plant of the Indian subcontinent that belongs to the family Fabaceae was chosen. The plant is well known for its precautionary action in tuberculosis. It has been established to possess some pharmacological activities such as membranes Stabilizing activity1, antibacterial2, anti-nociceptive3, thrombolytic activity4, antioxidant5, anthelmintic6, anti-diarrheal7, Hepato-protective 8. Phytoconstituents present in Bauhinia acuminata obey Lipinski's rule (MiLog P